Equal BER performance in linear successive interference cancellation for CDMA systems. - Buehrer, R.M (IEEE Transactions on communications)
In this contribution, we calculate the received power distribution required to obtain equal bit-error rate (BER) performance for all links in a code-division multiple-access system employing a linear successive interference cancellation (SIC) receiver at the base station for an additive white Gaussian noise channel. We show that the variance of the decision statistic of the linear SIC receiver can be formulated in a nonrecursive manner that allows calculation of the power profile necessary to obtain equal signal-to-noise-plus-interference ratios for all received signals when cancellation order is determined based on average power. When equal BER performance is required, this formulation allows capacity limits to be determined for a required signal-to-interference-plus-noise ratio (SINR) or an SINR limitation to be calculated for a given capacity. We also show that the power profiles required are significantly larger than those obtained when perfect cancellation is assumed, highlighting the inadequacy of such an assumption